Renewable Solar Energy Resources Potential and Strategy in Azerbaijan - Huseynli, Bahman (International Journal of Energy Economics and Policy, 2023)
Solar energy is an inexhaustible and pollution-free energy source that plays a significant role in the sustainable provision of energy services. The main purpose of this study is to examine the potential, current situation, future strategies, and policies of solar energy, which is a renewable resource in Azerbaijan. This study is research in which qualitative methods are used and within the scope of the study, literature review, systematic approach and inductive methods were used. In the study, Azerbaijan’s policy towards solar energy has been examined based on the potential sources of solar energy, the current situation and the country’s future strategies. Azerbaijan is slightly behind in the production of electricity from renewable energy sources. Along with all this, the most important strategic goals for the use of renewable and alternative energy sources in Azerbaijan have been defined. Thus, by 2030, the share of renewable energy investment in the country’s total energy balance to 30% has been determined as the main goal. As a result of the study, it can be said that solar energy policies will have a positive effect on the country’s economy in the coming years, since Azerbaijan has a geographical location and an infrastructure system that can be delivered to the countries in need.